Il nuovo intelligence dei diritti umani. Inedite architetture di prevenzione e sicurezza nell’impiego dei caschi blu - Montuoro, Umberto (Rivista di studi politici internazionali, 2022)
The Secretary General of the United Nations wanted to repair the serious image damage suffered in the past by the organization because of the reprehensible sexual conduct of some peacekeepers. There is a clear need for a radical change in approach to the specific question, as well as for the visibility of the exact proportions of the phenomenon was due to a lack of appropriate tools to combat it. Increased international judiciary and investigational cooperation appeared to be from the outset an indispensable prerequisite. Such urgent demands for justice now translate into the identification of new trial procedures and unprecedented forms of cooperation. This cooperation needs to be achieved not only between the State in whose territory the peacekeepers are operating and the State that sent the staff being investigated, but also needs to be framed within the Un. On the one hand, the Un should provide a more real support to national authorities in finding sources of evidence in the immediacy of the facts, while on the other hand, States must provide appropriate information to the Un. The determination of disciplinary and criminal facts is up to the legal systems, but the adoption of appropriate preventive measures and intelligence must be consciously and directly supported by the strategic direction of the Departement of Peacekeeping Operations (Dpko), as well. Surprising new areas of international cooperation are now opening. In addition, a further complementary plan of action is consolidating. The existence of an intelligence component in the United Nations is a force multiplier. An effective intelligence umbrella coverage can make the difference between life and death for dozens of peacekeepers and civilians involved in numerous terrorist attacks in recent years.